SINERGI GURU DAN ORANG TUA DALAM PENGEMBANGAN PENDIDIKAN AKIDAH AKHLAK KELAS VII DI MTS YASPURI MALANG - Siti Nur Azizah; Ibnu Jazari; Yorita Febry Lismanda (VICRATINA, 2020)
A child gets guidance and teaching from the teacher and parents, but in the scope of the family, parents are tasked with teaching the creed and supervising their children. The experience of teachers and parents is the main thing to determine the quality and quality of education. To achieve good synergy, teachers and parents need to understand several things that are the goal. Teachers don't just convey theories, and parents don't just feed children. But have the responsibility and guide and solve problems faced by students. In accordance with the research context, the focus of the problem here explains about 1) supporters and inhibitors in the development of the 7th grade morality subjects at poor MTs Yaspuri Malang, 2) the synergy of teachers and parents in the development of moral subjects in MTs Yaspuri Malang. The research used is qualitative, with a descriptive approach and data collection through observation, interviews and also documentation. The results showed the synergy of teachers and parents were able to establish harmonious relationships between teachers and parents, and be supportive for children, and have a sense of security, and form personal and good attitudes.